2010
DOI: 10.5194/os-6-775-2010
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycles of surface layer salinity in the Pacific Ocean

Abstract: Abstract. The seasonal variability of surface layer salinity (SLS) is examined in the Pacific Ocean between 40 • S and 60 •

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 36 publications
5
57
0
Order By: Relevance
“…Foltz and McPhaden (2008) looked at the seasonal variability of SSS in three regions in the Atlantic, one in the central North Atlantic with a weak seasonal cycle and two in the tropical Atlantic and western North Atlantic with stronger ones. Bingham et al (2010;henceforth BFM) examined the seasonal cycle of SLS in the Pacific Ocean between 40 • S and 60 • N. They found areas with large seasonal variation in the northern tropical Pacific, under the ITCZ, along the western and northern boundary of the North Pacific, and in the central South Pacific loosely centered around 10 • S. They compared these variations to the corresponding atmospheric fluxes of evaporation (E), precipitation (P ), and E − P . They also examined one of the advection terms and the entrainment term in the equation for SSS evolution and found them to be important in limited areas.…”
Section: F M Bingham Et Al: the Seasonal Cycle Of Surface Layer Samentioning
confidence: 99%
“…Foltz and McPhaden (2008) looked at the seasonal variability of SSS in three regions in the Atlantic, one in the central North Atlantic with a weak seasonal cycle and two in the tropical Atlantic and western North Atlantic with stronger ones. Bingham et al (2010;henceforth BFM) examined the seasonal cycle of SLS in the Pacific Ocean between 40 • S and 60 • N. They found areas with large seasonal variation in the northern tropical Pacific, under the ITCZ, along the western and northern boundary of the North Pacific, and in the central South Pacific loosely centered around 10 • S. They compared these variations to the corresponding atmospheric fluxes of evaporation (E), precipitation (P ), and E − P . They also examined one of the advection terms and the entrainment term in the equation for SSS evolution and found them to be important in limited areas.…”
Section: F M Bingham Et Al: the Seasonal Cycle Of Surface Layer Samentioning
confidence: 99%
“…Salinity anomalies tend to be more persistent than SST, and are more strongly influenced by oceanic advection/mixing [ Spall , 1993; Hall and Manabe , 1997; Mignot and Frankignoul , 2003, 2004]. The important role of the advection processes in governing the regional salinity has been documented by many studies [e.g., Delcroix and Hénin , 1991; Johnson et al , 2002; Rao and Sivakumar , 2003; Reverdin et al , 2007; Foltz and McPhaden , 2008; Ren and Riser , 2009; Bingham et al , 2010]. Yet, there are also numerous studies showing the dominance of E‐P on near‐surface salinity variations in the tropical oceans [e.g., Delcroix et al , 1996; Boyer and Levitus , 2002; Foltz and McPhaden , 2008; Bingham et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The important role of the advection processes in governing the regional salinity has been documented by many studies [e.g., Delcroix and Hénin , 1991; Johnson et al , 2002; Rao and Sivakumar , 2003; Reverdin et al , 2007; Foltz and McPhaden , 2008; Ren and Riser , 2009; Bingham et al , 2010]. Yet, there are also numerous studies showing the dominance of E‐P on near‐surface salinity variations in the tropical oceans [e.g., Delcroix et al , 1996; Boyer and Levitus , 2002; Foltz and McPhaden , 2008; Bingham et al , 2010]. For instance, Delcroix and Hénin [1991] analyzed the salinity measurements acquired along the tropical Pacific ship‐of‐opportunity tracks and showed that more than 40% of seasonal salinity variability in the Intertropical Convergence Zone (ITCZ) can be attributed to the E‐P forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Taurine is a nontoxic substance and osmolyte for cells, which can regulate internal amino acid levels to avoid any damage if faced with a change in osmolarity [32]. Bingham et al [5] indicated a seasonal variability of marine salinity around Japan with a large amplitude in winter. Thus, bottlenose dolphins could endure an immediate change in osmolarity and the high density of osmolarity that occurs during winter.…”
Section: Discussionmentioning
confidence: 99%